Geographic and Demographic Bank Outreach: Evidence from Germany's Three-Pillar Banking System - Alexander Conrad; Doris Neuberger; Maria Schneider-Reißig (Kredit und Kapital, 2009)
Geographic and Demographic Bank Outreach: Evidence from Germany's Three-Pillar Banking System This paper investigates the performance of Germany's three-pillar banking system in providing financial services nationwide, regarding different outreach indicators. At the federal state level, bank outreach shows South-North and West-East gaps. Combining regional and bank data at the district level for 2005, we examine the determinants of geographic and demographic branch penetration of the regional savings and cooperative banks. Both banking groups provide a larger branch penetration in more wealthy regions, but maintain a larger number of branches per inhabitant in less densely populated regions, easing access to retail banking services. With their comparatively large branch penetration in less wealthy regions, public savings banks help to reduce regional economic disparities. The branch penetration of both banking groups increases with the share of elder people and bank size in a region. Because of their public mission to serve all regions, public savings banks foster competition. (JEL G21, L1, L2) – – Geografische und demografische Reichweite von Banken: Empirische Evidenz für Deutschlands Dreisäulen-Bankensystem Der Beitrag untersucht die flächendeckende Bereitstellung von Finanzdienstleistungen durch das deutsche Dreisäulen-Bankensystem, wobei unterschiedliche Indikatoren der Reichweite betrachtet werden. Auf der Ebene der Bundesländer zeigen sich Süd-Nord- und West-Ost-Gefälle. Durch Verknüpfung von Regionalund Bankdaten auf Kreisebene für das Jahr 2005 werden die Determinanten der geografischen und demografischen Bankstellenpenetration der regional tätigen Sparkassen und Genossenschaftsbanken untersucht. Beide Bankengruppen zeigen eine höhere Bankstellenversorgung in wirtschaftsstärkeren Regionen, unterhalten aber mehr Bankstellen pro Einwohner in dünner besiedelten Regionen, womit sie den Zugang zu Finanzdienstleistungen erleichtern. Mit ihrer relativ großen Bankstellenpenetration in wirtschaftsschwächeren Regionen tragen die Sparkassen zur Überwindung regionaler ökonomischer Disparitäten bei. Die Bankstellenversorgung beider Regionalbankgruppen steigt mit dem Anteil älterer Menschen und der Bankgröße in einer Region. Durch ihren öffentlichen Auftrag, alle Regionen zu versorgen, tragen die Sparkassen zur Sicherung des Wettbewerbs bei.
Keywords: G21; L1; L2; 330